Physiotherapy Program on Claw Hand Condition at Leprosy Hospital Kelet Donorejo: a Case Study - Hawari, Dadang; Naufal, Adnan Faris; Prihastomo, Teguh (Academic Physiotherapy Conference Proceeding, 2022)
Introduction: Leprosy or known as Morbus Hansen's disease is a bacterium that attacks skin tissue, peripheral nerves, and respiratory tract in humans under the name Mycobacterium leprae. Fourteen countries including Indonesia conducted data collection on cases of leprosy in the world with a total of 199,992 people in 2015 and 17,202 people in Indonesia. Most people with leprosy experience ulnar nerve paralysis which causes partial disruption of the fingers.Case Presentation: Patient S, 21 years old, complains of swelling of the hands and itching and fever. The patient reported numbness in the left hand and difficulty moving the 4th and 5th fingers of the left arm. In January 2021 the doctor recommended taking multi drug therapy (MDT), after taking it the patient had a severe reaction with nodules appearing in several areas.Management and Outcome: Physiotherapy performed an IPPA examination (inspection, palpation, percussion, auscultation), the results were thickening of the left ulnar nerve, the skin surface felt dry and rough. physiotherapy also performs pain assessment using a numerical rating scale (NRS), muscle strength examination using manual muscle testing (MMT), examination of joint range of motion with a goniometer, examination of motor nerve function and nerve palpation with POD, and examination of functional ability of the hand using a wrist hand. disability index (WHDI).Discussion: The physiotherapy program carried out for claw hand patients aims to increase the range of motion of the joints, increase muscle strength, and increase the patient's functional activities.Conclusion: The physiotherapy program for 7 meetings on claw hand conditions at the Leprosy Hospital Kelet Donorojo, Jepara in the form of stretching, strengthning, and functional exercises can increase the range of motion of the joints, there has not been an increase in muscle strength and functional in the patient, although in the range of joint motion which increases, the results are not significant.